ROLE OF UBIQUITIN PROTEASOME SYSTEM IN GASTRIC CANCER PATHOGENESIS - E. V. Ivanova; I. V. Kondakova; О. V. Cheremisina; S. G. Afanasyev (Сибирский онкологический журнал, 2016)
The review presents data on the ubiquitin-proteasome system participation in pathogenesis of gastric cancer. The role of proteasome system in regulation of cell cycle, angiogenesis and tumor metastasis has been shown. The aspects of the participation of ubiquitin-proteasome proteolytic system in the pathogenesis of intensive muscle protein degradation in cancer cachexia are analyzed. The role of proteasome system in the development of H. Pylori-induced gastric cancer is discussed. The clinical assessment of selective proteasome inhibitor (bortezomib) is a promising area of research for metastatic gastric cancer.